Horacio Jorge Becco, "Don Segundo Sombra" y su vocabulario. Ediciones Ollantay, Buenos Aires, 1952; 161 pp. - Lope Blanch, Juan M. (El Colegio de México, 1955)
Se reseñó el libro: "Don Segundo Sombra" y su vocabulario.